Pemberian Stimulasi Pertumbuhan dan perkembangan oleh Ibu Berhubungan Dengan Perkembangan Anak Usia 1-3 Tahun - Devi Nurhayati; Latifah Susilowati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Children entering the age of 1-3 years of development stage whose behavior starts to be influenced by the external environment and family environment that must provide good stimulation for children. Mother's behavior about stimulation is assessed as a basic need to hone child development and improve her abilities. The purpose of this study was determined the correlation between maternal behavior about growth and development stimulation with the development of children aged 1-3 years in Depok, Sleman, Yogyakarta. This study was used descriptive analytic method with cross sectional approach. 79 mothers and children taken by purposive sampling technique. Researchers collected data on respondents when mothers and children came to the posyandu. Respondents who were not present at the posyandu, the researchers collected data through home visits. The mother filled out a questionnaire about the mother's behavior in giving stimulation of child growth and development first, then the researcher conducted development using Denver II. The data collected was analyzed using the Spearman test. The most of mothers had good behavior in the stimulation of child growth and development that is 65 respondents (82.2%), and most of the children in the normal category are 58 respondents (73.4%). Based on Spearman's test the p value = 0.016 so that there is a relationship between maternal behavior about growth and development stimulation with child development, and the value of the closeness of a weak relationship is 0.269. There is a correlation between maternal behavior regarding growth and development stimulation with the development of children aged 1-3 years. Keywords: mother behavior; stimulation; growth and development; children aged 1-3 years ABSTRAK Orang tua terutama ibu harus memberikan stimulasi yang baik bagi anak. Perilaku ibu tentang stimulasi merupakan kebutuhan dasar untuk mengasah perkembangan anak dan meningkatkan kemampuannya. Tujuan dari penelitian untuk mengetahui hubungan perilaku ibu dalam pemberian stimulasi pertumbuhan dan perkembangan dengan perkembangan anak usia 1-3 tahun di Depok, Sleman. Sampel dalam penelitian ini berjumlah 79 ibu dan anak diambil dengan teknik purposive sampling. Peneliti melakukan pengambilan data pada responden saat ibu dan anak datang ke posyandu. Bagi calon responden yang tidak hadir pada saat posyandu maka peneliti melakukan pengambilan data melalui kunjungan rumah. Ibu mengisi kuesioner tentang perilaku ibu dalam pemberian stimulasi pertumbuhan dan perkembangan anak terlebih dahulu selanjutnya peneliti melakukan pemeriksaan pertumbuhan dan perkembangan pada anak menggunakan Denver II. Data dianalisis menggunakan uji Spearman. Sebagian besar Ibu memiliki perilaku baik dalam stimulasi pertumbuhan dan perkembangan anak yaitu 65 responden (82,3%) dan sebagian besar anak perkembangannya dalam kategori normal yaitu sebanyak 58 responden (73,4%). Berdasarkan uji Spearman hasil nilai p=0,016 sehingga ada hubungan antara perilaku ibu dalam pemberian stimulasi pertumbuhan dan perkembangan dengan perkembangan anak, dan nilai keeratan hubungan lemah yaitu 0,269. Ada hubungan antara perilaku ibu tentang stimulasi pertumbuhan dan perkembangan dengan perkembangan anak usia 1-3 tahun. Kata kunci: perilaku ibu; stimulasi; pertumbuhan dan perkembangan; anak usia 1-3 tahun